ANALYSIS ON THE TOTAL QUALITY MANAGEMENT (TQM) PRACTICES TOWARDS BUSINESS PERFORMANCE; A CASE STUDY - Muhammad Isradi Zainal; Wahyu Ismail Kurnia; Kuswandi Arifin; Seherdi Siman (School of Business, Bogor Agricultural University (SB-IPB), 2021)
The improvement of company management quality to achieve competitive advantage must be appropriate in the term of applying the concept or strategy of improvement, because it can affect the company's success in competition with its competitors. Total Quality Management (TQM) is one of the concepts which is in regard with improving the quality of company management by considering almost all company aspects. It is proven through the claim of most academics and practitioners who say that TQM can improve company's business performance. This research aims to find out the implications of TQM practices on the business performance of PT. XYZ which is engaged in cement business. There are 10 TQM indicators and 3 company’s business performance indicators used, as well as 250 respondents who involved in this research. The approach of Structural Equations Modeling (SEM) is used in data processing and analysis. The software used are SPSS version 22 and SPSS-AMOS version 21. The results show that the practices of TQM have a positive effect on company’s business performance significantly. Moreover, each constructs of TQM variables and company's business performance show the adequate level of validity and is declared as capable in representing each variable. After all, this research is adequate to prove that TQM practices can significantly bring positive impact towards the business performance of XYZ Ltd. Keywords: business performance, competitive advantage, management quality, structural equations modeling (SEM), total quality management (TQM)